Adsorption and sensing of an anticancer drug on the boron nitride nanocones; a computational inspection. Issue 2 (25th January 2021) - Wang, Chao; Shen, Lizhen; Wu, Liang
Abstract: The electrical response of boron nitride nanocones (BNNCs) to 5-Fluorouracil (5FU) drug was investigated by first-principle density functional theory (DFT). The adsorption of 5FU causes a significant decrease in the BNNCs HOMO-LUMO gap (from 4.60 to 3.39 eV), thereby, the electrical conductivity has also increased. It indicates that the BNNCs could be an appropriate candidate for 5FU detection and may be used in the electronic sensors. Furthermore, the work function of BNNCs is influenced by the 5FU adsorption and the work function of BNNCs is reduce about 18.99%, it could also be a work function based sensor for the detection of 5FU. The BNNCs have also the advantage of short recovery time about 4.25 ms for desorption of 5FU.